Outcome of Clavicle Fractures Treated by Various Modalities - M T Ganesh; Haemanath Pandian; Aizel Sherief Palasseril (Journal of Orthopaedic Case Reports)
Introduction: Clavicle fractures account for a significant proportion of shoulder girdle injuries, with varying treatment modalities employed, ranging from conservative management to surgical intervention. This study aims to evaluate the outcomes of clavicle fractures treated conservatively versus those treated with open reduction and internal fixation (ORIF). Materials and Methods: A retrospective analysis was conducted on 94 patients with clavicle fractures treated between 2019 and 2023. Patients were categorized into two groups: those receiving conservative treatment (n = 52) and those undergoing surgical intervention (n = 42), which included intramedullary fixation using titanium elastic nail system (TENS) and plate and screw fixation. Clinical and radiological data were collected, and outcomes were assessed based on union rates, complications, and functional recovery. Results: The average time to solid union was 3 months, with conservative treatment yielding a mean of 4.9 weeks for middle-third fractures and 5.8 weeks for lateral-third fractures. The surgical group showed slightly longer healing times (mean 9.3 weeks for middle-third fractures and 10.2 weeks for lateral-third fractures) but achieved higher union rates, with only 2 cases (4.76%) of non-union in the TENS group. In contrast, the conservative group had a non-union rate of 7.69%, predominantly in lateral-third fractures. Malunion occurred in 85% of conservatively treated cases, yet functional impairments were minimal. Surgical intervention resulted in no reported deformities or significant functional deficits. Conclusions: While conservative treatment is effective for non-displaced fractures, surgical intervention offers significant advantages for displaced fractures, particularly in achieving higher union rates and better functional outcomes. This study reinforces the importance of personalized treatment strategies, emphasizing surgical management in cases of displacement or comminution to minimize complications and improve patient satisfaction.